EU Travel and Tourism Industry - A Cluster Analysis of Impact and Competitiveness - DANIEL BULIN (Global Economic Observer)
The tourism industry has known a sustained growth in recent decades, this sector taking advantage of the capacity to generate added value regardless of the type of capital input. The impact of tourism on the economy is indisputable, but the efficiency and the competitiveness provide a sustainable development of this industry. The EU enlargement, geographical and numerical, provides both-a diversity of tourism destinations and an opportunity for growth, considering widening of single market. This paper aims to assess tourism in the European Union, considering the impact and value of the tourism multiplier effect in economy, respectively efficiency and competitiveness of tourism. This paper proposes a classification of EU countries based on cluster analysis, using K-means algorithm.